Brucella Endocarditis Presenting With Findings Resembling Vasculitis - Fatih YILDIZ,; Ertuğrul BAYRAM,; Bayram KELLE,; Eren ERKEN, (Archives of Rheumatology, 2015)
Brucellosis is a zoonotic infection presenting with several systemic clinical symptoms. Cardiovascular involvement is observed in very rare of patients with brucellosis and the common involvement form is endocarditis. Heart failure is the prominent complication which may occur as a result of endocarditis. This type of infection may cause clinical symptoms including hematuria, proteinuria, and renal insufficiency. In this article, we report a patient with Brucella endocarditis resembling systemic vasculitis including hematuria, uremia, polyneuropathy, and epididymoorchitis findings.